2016
DOI: 10.1111/bij.12734
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and DNA barcoding confirm cryptic species in the African freshwater oysterEtheria ellipticaLamarck, 1807 (Bivalvia: Etheriidae)

Abstract: Recent molecular approaches to taxonomy have led to a steady increase in the identification of cryptic species. Within the Etheriidae, the species Etheria elliptica (freshwater oyster) is widespread and common and exists in most of the major African drainages. Within the African freshwater ecosystems, there are major threats to biodiversity and cryptic species complicate conservation strategies; unknown species exist and no conservation status has been assigned. Our objective here was to determine if E. ellipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…COI has been proven to be an appropriate DNA barcoding marker in the animal kingdom due to its relatively easy amplification and fewer numbers of insertions and deletions [ 12 ], also in suborder Heteroptera [ 13 , 14 , 15 ]. Many studies based on COI DNA barcoding sequences have shown its strength in species identification and defining the cryptic species in known species [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…COI has been proven to be an appropriate DNA barcoding marker in the animal kingdom due to its relatively easy amplification and fewer numbers of insertions and deletions [ 12 ], also in suborder Heteroptera [ 13 , 14 , 15 ]. Many studies based on COI DNA barcoding sequences have shown its strength in species identification and defining the cryptic species in known species [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many of these studies, unionid genera or species that had been identified by morphological characters were not consistent with those revealed through molecular phylogenetic analyses (e.g., Campbell and Lydeard, 2012a,b;Nagel and Badino, 2001;Roe and Hoeh, 2003). Although the vast majority of these molecular studies have focused almost exclusively on North American and European taxa, geographic and taxonomic sampling has recently increased, particularly in Africa (Elderkin et al, 2016;Graf, 2013;Whelan et al, 2011) and Asia (Huang et al, 2002;Graf, 2013, 2015;Zhou et al, 2007;Zieritz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in developing improved phylogenetic hypotheses for the Unionidae have occurred in the past several decades (Davis 1984; Lydeard et al 1996; Nagel and Badino 2001; Hoeh et al 2001, 2002; Giribet and Wheeler 2002; Graf 2002; Campbell et al 2005; Zanatta and Murphy 2006; Graf and Cummings 2007; Campbell and Lydeard 2012a, b; Froufe et al 2014; PriĂ© and Puillandre 2014; Graf et al 2015; Pfeiffer and Graf 2015). Most of these studies have focused on North American, Australian, and European taxa, although more recently, African (Whelan et al 2011; Graf 2013; Elderkin et al 2016) and Asian (Huang et al 2002; Zhou et al 2007; Huang et al 2013; Bolotov et al 2017a, b) taxa have been included, and a global phylogenetic framework of the Unionidae has recently been established (Bolotov et al 2017a; Lopes-Lima et al 2017a). Despite these advances, the incorporation of Asian taxa into unionid phylogenetic hypotheses, particularly those from China has lagged.…”
Section: Introductionmentioning
confidence: 99%